Elections and Revolutionary Board. Villavicencio 1947-1948 (2011)
Despite its geographical isolation with the center of the country, the city of Villavicencio was directly affected by the Gaitanismo movement and the Political movement that took place in Colombia during the years 1946 to 1948. Since then, in the capital of Intendencia of Meta, under a unique cultural context in the Orinoco region, particular forms of violence and the exertion of regional policy were presented, which were characterized by: state weakness, political control of a local elite, struggle for local power and exclusion of popular sectors. This paper shows then the above aspects in order to provide the construction of a not depleted historiography of the Colombian violence.